DEVELOPING OF CALCULUS TEACHING MATERIALS BASED ON AUDIOVISUAL - Akbar Nasrum; Herlina Herlina (IKIP Siliwangi and I-MES, 2019)
Millennials community right now prefer video media as a learning resource rather than reading textbooks. To understand the contents of books, we need to have a reasonably high literacy ability. Unlike the case with learning videos, explanations accompanied by images in the video can help someone to understand the material in that media. The first goal of this study was to make audiovisual teaching materials that could serve as a supplementary textbook teaching materials. The second goal was to test the effectiveness of teaching materials that have been created. The method used was the development method using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The process of developing teaching materials began with creating multimedia learning, recording stages, editing stages, and completion stages. Material experts and media experts then validated the teaching materials that had been produced and tried out on students. The results of the try out documents to the students showed that there were significant changes both in terms of motivation, enthusiasm for learning, interaction in the classroom, and from student learning outcomes. These results made the student's response to the use of teaching materials excellent. This audiovisual teaching material was worthy and effectively of being used as a learning media, both as a supplementary or primary source.